How biomass growth mode affects ammonium oxidation start-up and NOB inhibition in the partial nitritation of cold and diluted reject water - Kouba, Vojtěch; Svehla, P; Catrysse, M; Prochazkova, L; Radechovska, H; Jenicek, P; Bartacek, J (Environmental technology, 2019)
The inhibition of undesirable nitrite oxidizing bacteria (NOB) and desirable ammonium oxidizing bacteria (AOB) by free ammonia (FA) and free nitrous acid (FNA) in partial nitritation (PN) is crucially affected by the biomass growth mode (suspended sludge, biofilm, encapsulation). But, the limitations of these modes towards less concentrated reject waters (≤600 mg-N L-1) are unclear. Therefore, this work compares the start-up and stability of three PN sequencing batch reactors (SBRs) with biomass grown in one of the three modes: suspended sludge, biofilm and biomass encapsulated in polyvinyl alcohol (PVA) pellets. The SBRs were operated at 15°C with influent total ammonium nitrogen (TAN) concentrations of 75-600 mg-TAN L-1. PN start-up was twice as fast in the biofilm and encapsulated biomass SBRs than in the suspended sludge SBR. After start-up, PN in the biofilm and suspended sludge SBRs was stable at 150-600 mg-TAN L-1. But, at 75 mg-TAN L-1, full nitrification gradually developed. In the encapsulated biomass SBR, full nitrification occurred even at 600 mg-TAN L-1, showing that NOB in this set-up can adapt even to 4.3 mg-FA L-1 and 0.27 mg-FNA L-1. Thus, PN in the biofilm was best for the treatment of an influent containing 150-600 mg-TAN L-1.
Keywords: biomasa; bioreaktory; amoniové sloučeniny; oxidace-redukce; Nitrites; odpadní vody; Bacteria; Ammonium Compounds; Oxidation-Reduction; dusitany; Sewage; Bioreactors; Biomass